Philosophical and Linguistic Laws of the Concept of Causality (Eurasian Journal of Philology Science and Education, 2024)
The article describes the consideration of functional grammar in the philosophic and linguistic sciences in the causal category, which is one of the new directions in linguistics. The concept of causality originates in the science of general philosophy. It follows the philosophical research that linguistics, including those considered as a special concept of functional grammar, is interpreted as a natural phenomenon. The fact that the study of global linguistics and Kazakh linguistics are formed on the basis of speech activity attracts the attention of scientists to the study in several aspects. It is proved that the causal category attracted the attention of philosophers to the search for motives, causes of the basic concepts of being in life, the reality that induced the interest of linguists.The article focuses on the integration of philosophical and linguistical patterns of the causal concept as a complex body within the framework of the interrelation of semantic levels of all linguistic groups, and not in a narrow sense. The disclosure of the semantic–functional purpose of causality shows that the nature of language and semantic aspects are various. Therefore, considering the activity of causal concepts from the point of view of the theory of the functional-semantic field, it is possible to fully recognize the nature of this category by specifying the paradigm and syntagmatic correlations of all linguistic means and revealing their semantic structure. At the same time, language levels that belong to the causal category can be considered not only grammatically, but also occupying a place in categories that can be expressed through other degrees of language. Therefore, causal progress falls into a philosophical and linguistic classification. In philosophy, it searches for the cause of the world, the creation, of being, in linguistics, it is conceptualized as a functional semantic category expressing the essence and content of this cause through a series of different linguistic operations. It is entrenched that the linguistic techniques that reveal the essence of causal semantics are very diverse, and its paradigm is proposed on the basis of scientific concepts for plain systematization.Keywords: functional grammar; function; causality; speech activity; functional-semantic field; categorical situation